1994
DOI: 10.1128/mcb.14.12.7855
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of platelet-derived growth factor- and epidermal growth factor-mediated mitogenesis and signaling in 3T3 cells expressing delta Raf-1:ER, an estradiol-regulated form of Raf-1.

Abstract: We have recently described the properties of delta Raf-1:ER, a fusion protein consisting of an oncogenic form of human Raf-1 and the hormone binding domain of the human estrogen receptor. In this study, we demonstrate that activation of delta Raf-1:ER in quiescent 3T3 cells (C2 cells), while sufficient to promote morphological oncogenic transformation, was insufficient to promote the entry of cells into DNA synthesis. Indeed, activation of delta Raf-1:ER potently inhibited the mitogenic response of cells to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 64 publications
4
66
2
Order By: Relevance
“…Because we obtain high levels of ERK2 activity in the MKK (AN3/S218E/S222D)-transfected cells, the effects that we observe are not likely to result from ERK inhibition by phosphatases. The mechanism of inhibition in our experiments therefore seems to be quite different from that occurring during ARaf-l:ERmediated inhibition of 3T3 cell growth (Samuels and McMahon, 1994).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Because we obtain high levels of ERK2 activity in the MKK (AN3/S218E/S222D)-transfected cells, the effects that we observe are not likely to result from ERK inhibition by phosphatases. The mechanism of inhibition in our experiments therefore seems to be quite different from that occurring during ARaf-l:ERmediated inhibition of 3T3 cell growth (Samuels and McMahon, 1994).…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, estrogen-induced ARaf-1 :ER prevents NIH 3T3 cell proliferation induced by tyrosine kinase-linked growth factors. This inhibition is correlated with phosphorylation of Sos and the activation of a vanadate-sensitive phosphatase that prevents ERK activation (Samuels and McMahon, 1994). Feedback inhibition of a molecule like Sos that functions early in the signaling pathway would be expected to switch off the entire pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In NIH3T3 ®broblasts the activation of an inducible oncogenic version of the cRaf-1 protein (c-Raf-1-BxB-ER TM ) has been shown to be su cient to drive cells arrested by serum starvation or cell density back into the cell cycle (Kerkho and Rapp, 1997). In the same cellular background a similar Raf construct was shown to block cell proliferation when activated (Samuels and McMahon, 1994;Pumiglia and Decker, 1997;Woods et al, 1997;Sewing et al, 1997). An explanation for these obvious di erences was recently found, when three groups showed that the activation of constitutive low Raf signals leads to cell proliferation and that very high constitutive Raf signals lead to a cell cycle arrest Woods et al, 1997;.…”
Section: Constitutive Activation Of Ras or Raf Induces Cyclin D1 Overmentioning
confidence: 89%
“…As noted for activated Ras (Franza et al, 1986;Hirakawa and Ruley, 1988), too much Raf signaling leads to cell cycle arrest rather than proliferation (Samuels and McMahon, 1994;Kerkho and Rapp, 1998;Woods et al, 1997;Zhu et al, 1998;Sewing et al, 1997). These observations suggest that high intensity Raf signals are recognized as inappropriate, leading to a block in cell cycle progression.…”
mentioning
confidence: 85%